PROBLEMS ENCOUNTERED BY STUDENTS IN ONLINE CREATIVE WRITING CLASS AND THE SOLUTIONS - Denny Satrya Andy Nugraha; Listyani - Listyani (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2021)
Writing is one of the main skills in learning English students should master. Creative Writing becomes one of the writing courses in the English Language Education Program (ELEP) of UKSW. This year, many institutes including UKSW conducted their learning by doing online classes. However, there may be some difficulties faced by students during their online classes. Therefore, this study aimed to analyze the problems faced by the students in online Creative Writing class and the solutions to overcome those problems. Thus, the research questions of this study are “What are the problems that are faced by the students in online Creative Writing class?” and “How do the students overcome the problems?” Twenty-three participants were involved in this study which used a mix of open-ended and closed-ended items in the questionnaire as the data collection instrument. The participants were 2020 students of ELEP, UKSW, Indonesia. From the data from the study, it was found that the problems faced by the students in their online Creative Writing class were the course materials, bad internet connection, students’ motivation, and teachers’ unclear explanations. Besides that, there were also four strategies used by the students to faced their difficulties such as, finding better connections, asking friends or lecturers, doing self-motivation, and learning the material after class. The findings from this study are expected to be helpful for teachers to know the problems faced by the students in online Creative Writing classes.